2019
DOI: 10.1177/1358863x19843180
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptors 2 and 6 mediate apoptosis and inflammation in ischemic skeletal myotubes

Abstract: Critical limb ischemia (CLI) is associated with skeletal muscle damage. However, the pathophysiology of the muscle damage is poorly understood. Toll-like receptors (TLR) have been attributed to play a role in ischemia-induced tissue damage but their role in skeletal muscle damage in CLI is unknown. TLR2 and TLR6 expression was found to be upregulated in skeletal muscle of patients with CLI. In vitro, ischemia led to upregulation of TLR2 and TLR6 by myotubes, and activation of the downstream TLR signaling pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Other groups have shown high glucose increases TLR4 mediated inflammation; however, the novel observation from this study is the effect of adding a second noxious variable, hypoxia. This group has previously shown hypoxia induces TLRs 2, 6, and 4 expression and activation in skeletal muscle; 29 however, it has now been demonstrated in dermal fibroblasts there is a significant increase in TLR4 expression and activation in hypoxia with concurrent exposure to high glucose. This inflammatory effect signals via TLR4 pathways, resulting in increased inflammation via downstream production of cytokines such as IL-6.…”
Section: Discussionmentioning
confidence: 95%
“…Other groups have shown high glucose increases TLR4 mediated inflammation; however, the novel observation from this study is the effect of adding a second noxious variable, hypoxia. This group has previously shown hypoxia induces TLRs 2, 6, and 4 expression and activation in skeletal muscle; 29 however, it has now been demonstrated in dermal fibroblasts there is a significant increase in TLR4 expression and activation in hypoxia with concurrent exposure to high glucose. This inflammatory effect signals via TLR4 pathways, resulting in increased inflammation via downstream production of cytokines such as IL-6.…”
Section: Discussionmentioning
confidence: 95%
“…Toll-like receptors (TLRs) are recognized as one of the main contributors to pathogen-induced, sterile, and ischemic injury-induced inflammation. 4,27 Endogenous ligands such as low-molecular hyaluronic acid, fibronectin, heat shock proteins, and heparin sulfate were found to be cleaved in inflamed tissue and to activate TLR2 and TLR4, initiating an inflammatory response even in the absence of pathogens and infiltrating immune cells. Both macrotrauma and microtrauma conditions occur in skeletal muscle injury.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggested that inflammation plays an important role in the progress of CLI ( 4 , 5 ). In support of this theory, it was shown that the circulating levels of cytokines (IL-6 and TNFα), adhesion molecules (VCAM-1 and ICAM-1), and selectins in patients with peripheral arterial disease are elevated ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous theories about the CLI etiology, including lipid deposition, inflammation, and thrombosis ( 2 , 3 ). Kinds of inflammatory factors and cytokines are involved in inflammatory injury, plaque formation, plaque rupture, and final artery stenosis or occlusion ( 4 , 5 ). Patients with peripheral arterial diseases often have accompanying kinds of severe comorbidities, including coronary artery disease, cerebrovascular disease, respiratory dysfunction, and end-stage renal disease ( 6 ).…”
Section: Introductionmentioning
confidence: 99%